Legal position of commitment making officers in government contracts - Disianto, Dimaz; Isnaeni, Isnaeni; Prasetyawati, Endang (Technium Social Sciences Journal, 2022)
This research is a normative legal research. The characteristics of Government Contracts are multi-faceted and have a special character, namely they are private with the dimensions of public law (civil law, and administrative law), which means that Government Contracts have a hybrid character. In government contracts, the Commitment Making Officer (CMO) by the Budget User/Budget User Proxy as a representative of the government is given the authority to make decisions and/or take legal action to enter into agreements and also issue funds sourced from the state budget/regional budget in procurement of goods/services. The nature of CMO's legal position in Government Contracts is a private legal subject and its legal actions are subject to private law. In this regard, the CMO can be civilly liable. Therefore, if the CMO makes a mistake, in this case it is in default, then the CMO can be sued for compensation to the Court as appropriate for individual legal subjects and private legal entities in general.